Convoy Drugs in Traditional Persian Medicine: The Historical Concepts of Bioavailability and Targeting - Nastaran Ebadi; Fatemeh Masoomi; Maryam Yakhchali; Seyede Nargess Sadati Lamardi; Mohammad Reza Shams-Ardakani; Omid Sadeghpour; Azadeh Raiesdana; Farid Ramezany (Tehran University of Medical Sciences, 2015)
Similar to other traditional medicines, Traditional Persian Medicine (TPM) applies its special terms for description of drug functions. Among these functions, convoy (Mobadregh) medicines are unique, mainly due to the interaction of them with the pharmacokinetics of other herbal medicines. These interactions  suggest  the  potential  herb-herb  and  herb-synthetic  drug  interactions  with  convoy medicines that necessitate the study and precise definition of them. For this purpose, old Persian medical texts and pharmacopeias were searched and investigated for the name of convoys, their target organ(s), primary qualities, and other functions. Relationships among convoy and other functions based on notes on the texts and statistical analysis were considered. Based on the old resources, the convoys were defined as modifiers (of drug actions), which facilitate access of drugs and foods to whole body or organs. The concept of targeting in some convoys was also implied as well as other disciplines such as Traditional Chinese Medicine and Ayurveda. Descriptive analysis of the available data showed that most of the convoys contain warm and dry primary qualities. Anti-blockage and thin consistencies are main characteristics of this class of drugs. Statistical analysis also showed diuretic activity is another major characteristic of them. Other functions such as discutient, attenuant, and tonic are capable to assist convoying by thinning of humors and organs. Analysis of TPM literature shows the presence of a logic approach in the formulation of compound drugs. Owing to the potential influence of convoys on the pharmacokinetic profile of other herbs and synthetic drugs, it is necessary to conduct future studies to evaluate these interactions in TPM and modern medicine.